(untitled) (TAJ: Journal of Teachers Association, 2022)
Background: Hepatitis C virus (HCV) has been described as a significant causative agent of chronic hepatitis since its characterization in 1989. HCV may remain latent or become activated, leading to persistent infections and, in some cases, cirrhosis and hepatocellular carcinoma HCV is most commonly transmitted through direct contact with infected blood. Other, less common routes of transmission of HCV include sexual intercourse with infected individuals and mother to child transfer. Materials and Methods: This is a cross-sectional descriptive type study which was carried out in the Department of Transfusion Medicine of Rajshahi Medical College Hospital for six months from January to June 2014 to determine the prevalence of hepatitis C virus in the apparently healthy blood donors. All apparently healthy blood donors fulfilling the inclusion and exclusion were included in this study. The blood donors who were positive for anti-HCV antibodies were seropositive. Anti HCV antibody screened by ICT and confirmed by ELISA method. Results: Among 1712 apparently healthy blood donors, 36 (2.1%) donors were anti-HCV positive, and 1676 (97.9%) donors were negative. The mean age of the study patients was 34.05 years (SD = ± 8.79). 66.7% of the study patients were male, whereas 33.3 % of donors were female among the 36 blood donors. Conclusion: It is absolutely necessary to avoid the transmission of infection from repeat donors who are asymptomatic HCV positive. Policymakers and public health stakeholders need to introduce and implement further preventive measures targeting the routes of HCV transmission. TAJ 2021; 34: No-2: 24-31